2010
DOI: 10.1109/tbme.2010.2046485
|View full text |Cite
|
Sign up to set email alerts
|

Ranking the Influence of Tissue Conductivities on Forward-Calculated ECGs

Abstract: This paper examined the effects that different tissue conductivities had on forward-calculated ECGs. To this end, we ranked the influence of tissues by performing repetitive forward calculations while varying the respective tissue conductivity. The torso model included all major anatomical structures like blood, lungs, fat, anisotropic skeletal muscle, intestine, liver, kidneys, bone, cartilage, and spleen. Cardiac electrical sources were derived from realistic atrial and ventricular simulations. The conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 35 publications
7
118
1
Order By: Relevance
“…Impact of the complexity of the patient-specific geometry (organs and their conductivities in the volume conductor model) on surface potentials was studied by Doessel [21] and Zemzemi [22]. Global study of the influence of the torso inhomogeneities on atrial and ventricular ECG signals was performed in [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impact of the complexity of the patient-specific geometry (organs and their conductivities in the volume conductor model) on surface potentials was studied by Doessel [21] and Zemzemi [22]. Global study of the influence of the torso inhomogeneities on atrial and ventricular ECG signals was performed in [21].…”
Section: Discussionmentioning
confidence: 99%
“…Global study of the influence of the torso inhomogeneities on atrial and ventricular ECG signals was performed in [21]. Realistic forward simulations showed that the conductivity of blood in the main vessels had high impact on the atrial signals.…”
Section: Discussionmentioning
confidence: 99%
“…These are also referred to as inhomogeneties. The various tissues, fluids, and structures are known to vary with respect to their conductivities (1). Hence the mentioned torso model includes all major anatomical structures like blood, lungs, fat, anisotropic skeletal muscle intestine, liver, kidneys, bone, cartilage and spleen.…”
Section: Torso Modelmentioning
confidence: 99%
“…Endocardial data acquisition is available for one of those patients as a way to evaluate the accuracy of activation time reconstruction. The analysis of those datasets requires performing several image-and signal-processing steps [31,39]. These include the wholeheart MRI segmentation for the endocardium of the ventricles and atria and epicardium of the left ventricles (LVs).…”
Section: Radiofrequency Ablationmentioning
confidence: 99%